2012
DOI: 10.1109/lpt.2012.2206378
|View full text |Cite
|
Sign up to set email alerts
|

High-Power Distributed Feedback Lasers With Surface Gratings

Abstract: We present the results for high-power broad-area distributed feedback lasers with surface gratings of 80th, 135th, and 270th Bragg orders. A maximum output power of 11 W for a laser with 80th order grating, emitting around 976 nm with a spectral width <1 nm has been achieved. Similar narrow linewidth operation occurs for devices with 135th Bragg order from 7-to 11-W output power. The technological approach to fabricating these devices based on stepper lithography and reactive ion etching is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
(10 reference statements)
1
5
0
Order By: Relevance
“…The vertical layer design selected contains a 2.4 µm thick low-doped confinement layer and has an refractive-index profile similar to that given in Tab. I. DFB lasers with a very high Bragg order as investigated here tend to lase also at wavelengths λ ∓ ∆λ belonging to neighbouring Bragg orders N ± 1 [5] because ∆λ ≈ 12 nm 1 for N = 80 and λ = 970 nm is too small to ensure stable single-longitudinal mode operation over a large power range due to the thermal detuning between gain peak (dλ p /dT ≈ 0.34 nm/K) and Bragg (dλ B /dT ≈ 0.08 nm/K) wavelengths. Therefore we show here results for a Bragg order N = 40.…”
Section: B Narrow-stripe Broad-area Lasermentioning
confidence: 90%
See 1 more Smart Citation
“…The vertical layer design selected contains a 2.4 µm thick low-doped confinement layer and has an refractive-index profile similar to that given in Tab. I. DFB lasers with a very high Bragg order as investigated here tend to lase also at wavelengths λ ∓ ∆λ belonging to neighbouring Bragg orders N ± 1 [5] because ∆λ ≈ 12 nm 1 for N = 80 and λ = 970 nm is too small to ensure stable single-longitudinal mode operation over a large power range due to the thermal detuning between gain peak (dλ p /dT ≈ 0.34 nm/K) and Bragg (dλ B /dT ≈ 0.08 nm/K) wavelengths. Therefore we show here results for a Bragg order N = 40.…”
Section: B Narrow-stripe Broad-area Lasermentioning
confidence: 90%
“…An implementation of a surface grating within the ridge allows a better overlap of the mode with the grating but complicates the p-contacting because of the interruption of the highly p-doped top layer. We found that even with very high Bragg orders > 10 it is possible to stabilize the wavelength and to reduce the spectral width of BA lasers if very narrow grooves are etched [4], [5]. The large grating periods enable a simple fabrication of the grating and the formation of an Ohmic p-contact with a low resistance.…”
Section: Introductionmentioning
confidence: 93%
“…As an alternative, surface gratings can be etched through the complete vertical structure or parts of it [6]. In [7,8] we have presented results of distributed feedback (DFB) BA lasers with 80th order Bragg gratings, achieving spectrally stabilized emission with a spectral width Δλ 95% <0.7 nm at output powers of P>6 W. However, the spacing between the 80th order mode and the neighboring Bragg modes is only 12 nm, so that the wavelength of maximal gain has to be optimized very carefully, considering the current induced temperature increase at the point of operation, to avoid lasing at higher or lower order grating modes. With uniform 40th order Bragg gratings in DFB-BA lasers suppress lasing in neighboring Bragg modes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, high-order surface gratings (HSGs) have been shown to narrow laser spectra [9][10][11]. The introduction of HSGs in DFB or DBR lasers enables a grating period of over 7 μm for orders greater than 30, which eases fabrication thereof.…”
Section: Introductionmentioning
confidence: 99%